Neuroimaging Findings as a Predictor of Choice of Antiepileptic Drugs for Seizure Control in West Syndrome (Bangladesh Journal of Child Health, 2018)
Background: West syndrome (WS) is a severe form of encephalopathy that typically affects young infants ranges from 2-3.5/10,000 live births. Approximately 50% causes of Infantile Spasm are associated with prenatal factors that includes congenital CNS malformations, intrauterine insults, neurocutaneous syndromes such as Tuberous sclerosis complex, metabolic disorders or genetic syndromes and have poor prognosis. For early identification of underlying etiology a proper neuroimaging is essential that will also help to predict the outcome. For this reason my study aimed to correlate the presence of neuroradiologic abnormalities and its impact on seizure control in the children with West syndrome.Methodology: This retrospective cross sectional study was carried out in Institute of Pediatric Neurodisorder and Autism (IPNA) in BSMMU. All patients those who were diagnosed as a case of West syndrome in between age of 3 months to 3 years according to ILAE (International League against Epilepsy) during period of June 2013 to May 2015 were included in this study.Results: Thirty one (31) children with West Syndrome were studied, their mean age of presentation was 18±10.48 months, mean age of onset of seizure was 6.68±3.9 months, 67.7% of them were male. Patients with normal neuroradiologic findings had early remission of spasms and with anomalies, atrophy and calcification were associated with poor response to drug (p=0.03). ACTH was the most commonly used drug with good seizure remission where neuroimaging finding was normal and in cerebral atrophy as a consequence of perinatal asphyxia (p=0.06). Vigabatrin showed good seizure remission in WS due to Tuberous Sclerosis Complex.Conclusion: Seizure prognosis of West Syndrome differ greatly according to the type of brain lesion so in every suspected cases of West Syndrome early neuroimaging should have to be performed for choosing an appropriate antiepileptic drug.Bangladesh J Child Health 2018; VOL 42 (1) :9-14